Green synthesis of anisotropic gold nanoparticles using cinnamon with superior antibacterial activity. (17th April 2019) - Goyal, Divya; Saini, Avneet; Saini, G S S; Kumar, Rajesh
Abstract: Stable gold nanoparticles have been synthesized by one step, cost effective and environment friendly technique at room temperature using the natural spice cinnamon. The synthesized nanoparticles have been characterized using Ultraviolet visible spectroscopy, x-ray diffraction, Fourier transform infrared spectroscopy and Transmission electron microscopy. Transmission electron microscopy images confirm the presence of spherical and anisotropic nanoparticles of different shapes that include triangular, hexagonal and some spherical shaped nanoparticles. The decreased symmetry of anisotropic nanoparticle gives rise to unique optical properties. The antibacterial activity of nanoparticles has also been studied.